Management of multiple myeloma - Alexanian, R.; Dimopoulos, M.A. (Seminars in Hematology, 1995)
After a sequence of standard and intensive therapies, approximately 70% of patients with multiple myeloma achieve a remission of good quality and of many months duration. Yet the disease remains incurable because the high residual burden of approximately 1010 tumor cells cannot be eradicated. Initial disease control, followed by long unmaintained or maintained remissions and by repeated recontrol of relapsing disease, provides the best chance for a long survival time of good quality. Since melphalan-prednisone became available, many other chemotherapy programs have been studied. For selected groups of patients, the most useful regimens are VAD, high-dose dexamethasone, high-dose alkylating agent therapy, and myeloablative therapy plus autologous cell transplantation. Other programs, such as treatments using combinations of alkylating agents in standard doses or interferon alfa, remain unproven despite prolonged study. Until the mortality rate associated with allogeneic bone marrow transplantation can be reduced substantially, the role of intensive treatment supported by this procedure will be limited. Current testing of agents such as paclitaxel, new agents that suppress MDR, topoisomerase I inhibitors, and myeloablative bone-seeking isotopes may lead to future improvements.